122 Cardiac Abnormalities are Common in Patients Diagnosed with Phaeochromocytoma as Detected by Cardiovascular Magnetic Resonance Imaging. (31st May 2014) - Ferreira, Vanessa; Marcelino, Mafalda; Piechnik, Stefan; Marini, Claudia; Karamitsos, Theodoros; Francis, Jane; Ranjit Arnold, J; Mihai, Radu; Thomas, Julia; Herincs, Maria; Korbonits, Marta; Hassan-Smith, Zaki; et al.
Abstract : Introduction: Sudden and/or chronic exposure to catecholamines may predispose patients with phaeochromocytoma to cardiac pathology, including left ventricular (LV) hypertrophy, myocardial infarction, stress-induced cardiomyopathy and heart failure. This is a prospective, multicentre study using cardiovascular magnetic resonance (CMR) imaging to describe the variety and incidence of cardiac abnormalities in patients diagnosed with phaeochromocytoma. Methods: Patients diagnosed with phaeochromocytoma (n = 50) were included. We prospectively recruited patients newly-diagnosed with confirmed phaeochromocytoma (n = 20, age 51 ± 14 yrs) who underwent CMR before and after curative surgical resection of the phaeochromocytoma (median follow-up 1 year). Previously-diagnosed patients who had curative surgery (n = 30, age 52 ± 14 yrs) were also recruited. Patients with known cardiac conditions were excluded. CMR included cine imaging for LV function, T2-weighted imaging for oedema and late gadolinium enhancement imaging to detect scarring. Results: In newly-diagnosed patients, the mean LV ejection fraction was 67 ± 10% (range 47–88%; normal range 57–81%); Of these patients, 20% (n = 4/20) had mild global LV dysfunction (EF 47–56%). A significant proportion (65%, n = 13/20) demonstrated scarring, all with a non-ischaemic pattern (midwall/subepicardial/patchy), but the areas were small (<10% myocardium); no patient had myocardial infarction (subendocardial scarring). One patient demonstrated global myocardial oedema with normal EF. All LV dysfunction or oedema were reversible and normalised at postoperative follow-up. Previously-diagnosed patients had a slightly higher EF of 73 ± 7% (56–86%) compared to newly-diagnosed patients (P < 0.03); only one (3%) had mild global LV dysfunction (EF = 56%). Compared to newly-diagnosed patients, a significantly smaller proportion of previously-diagnosed patients (17% vs. 65%; P < 0.001) demonstrated areas of scarring, which again were small in areas with a non-ischaemic pattern, except for one patient who suffered a small myocardial infarction. Conclusions: Cardiac abnormalities are common in patients newly-diagnosed with phaeochromocytoma, and include mild LV dysfunction, myocardial oedema and small areas of non-ischaemic scarring, with the former two demonstrating full reversibility and normalisation post surgical resection of the phaeochromocytoma. In patients who had previously undergone curative surgical resection of their phaeochromocytoma, the incidence of cardiac abnormalities is lower (17%), predominantly consisting of small areas of non-ischaemic fibrosis.